Recent Evidence on the Impact of Ramadan Diurnal Intermittent Fasting, Mealtime, and Circadian Rhythm on Cardiometabolic Risk: A Review - BaHammam, Ahmed S.; Almeneessier, Aljohara S. (Frontiers in Nutrition, 2020)
In this article, we reviewed recent data that examined the relationship of circadian rhythm, mealtime, and intermittent fasting with the risk of cardiometabolic dysfunction. We also examined the effect of their interactions on cardiometabolic risks. Furthermore, since major differences exists between Ramadan diurnal intermittent fasting compared to other forms of experimental intermittent fasting, in this article, we further restricted the discussion to Ramadan diurnal intermittent fasting. PubMed and Google Scholar databases were searched using “intermittent fasting”, “time-restricted feeding”, “fasting”, “mealtime”, “circadian rhythm,” and “cardiometabolic risk,” focusing on human studies published after 2013. Recent evidence indicates that meal timing may influence circadian rhythm, as a result, it may also directly or indirectly impact cardiometabolic risk. In humans, several studies suggested that late mealtime is related to an increased risk of poor cardiometabolic health. Nevertheless, large clinical interventional studies are required to assess causality between late mealtime and cardiometabolic morbidity. Currently, evidence indicates that Ramadan diurnal intermittent fasting has several beneficial effects that may reduce the risk of cardiometabolic disorders such as weight reduction, improvement in lipid profile and glycemic control, reduction in proinflammatory markers, and oxidative stress. Nevertheless, several changes in daily lifestyle routine, happening during the Ramadan month, may affect the all measured markers of cardiometabolic diseases. Summarily, no definitive conclusion about the impact of Ramadan intermittent fasting on oxidative stress can be formulated. Therefore, large, well-designed studies, which control for various confounding factors are required to assess the influence of Ramadan diurnal intermittent fasting on markers of cardiometabolic risk and disorders.